0379 A Randomized Controlled Trial Of CBT-I and CPAP For Comorbid Insomnia and OSA: Initial Findings from the MATRICS Study. (12th April 2019) - Ong, Jason C; Crawford, Megan R; Wyatt, James K; Fogg, Louis F; Turner, Arlener D; Dawson, Spencer C; Edinger, Jack D; Kushida, Clete A; Abbott, Sabra M; Malkani, Roneil G; Attarian, Hrayr P; Zee, Phyllis C
Abstract: Introduction: The purpose of this study was to compare the efficacy of three treatment sequences using CPAP with or without CBT-I for the treatment of comorbid insomnia and obstructive sleep apnea (COMISA). Methods: One-hundred and twenty-one adults (52.50% female, mean age=50.00) with COMISA were randomized to receive one of three treatment models using a partial factorial design: CBT-I followed by CPAP (Model A), CBT-I concurrent with CPAP (Model B), and CPAP only (Model C). CPAP was delivered following standard procedures for in-lab CPAP titration and home set-up with a third-party vendor. CBT-I was delivered in four individual sessions. Primary outcomes were CPAP adherence across the first 90 days of use and global measures of insomnia (Insomnia Severity Index; ISI) and sleep quality (Pittsburgh Sleep Quality Index; PSQI). Planned comparisons were conducted on those who received CBT-I+CPAP (Models A and B combined) versus CPAP only (Model C) using Wilcoxon signed ranks test and linear mixed models. Results: No significant differences were found between the CPAP+CBT-I groups versus the CPAP only group on percent of nights used (Median=48.65% vs Median=71.10%, p=.29), minutes used per night (Median=232.87 vs Median=186.06, p=.21) or percentage of participants who were regular CPAP users (≥4 hours on ≥70% of nights during 30-day period; 37.50% vs 36.59%, p=.92). For mild OSA (AHI≥5 and <15), the CPAP+CBT-I groups used CPAP on a greater percentage of nights compared to the CPAP only group (Median=30.00% vs Median=5.00%), which approached significance (p=.05). A significant main effect was found for improvement in the ISI (p<.0001) and PSQI (p<.0001) but the interaction was not significant for either measure. Conclusion: These findings indicate that patients with COMISA show improvements in self-reported global measures of insomnia and sleep quality across all treatment models. Although no significant benefits were found for those who received CBT-I+CPAP in the overall sample, there were indications that CBT-I might improve CPAP adherence among those with mild OSA. Support (If Any): This study was supported by grant R01HL114529 from the National Institutes of Health.